2015
DOI: 10.1002/cmdc.201500334
|View full text |Cite
|
Sign up to set email alerts
|

6‐Methyluracil Derivatives as Bifunctional Acetylcholinesterase Inhibitors for the Treatment of Alzheimer's Disease

Abstract: Novel 6-methyluracil derivatives with ω-(substituted benzylethylamino)alkyl chains at the nitrogen atoms of the pyrimidine ring were designed and synthesized. The numbers of methylene groups in the alkyl chains were varied along with the electron-withdrawing substituents on the benzyl rings. The compounds are mixed-type reversible inhibitors of cholinesterases, and some of them show remarkable selectivity for human acetylcholinesterase (hAChE), with inhibitory potency in the nanomolar range, more than 10,000-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 52 publications
(87 reference statements)
0
35
0
Order By: Relevance
“…4. We have previously reported significant differences in estimated binding energies for the same compounds with these targets [12]. Here, we show that the target X-ray structure determines whether or not ligand poses reflect mixed-type inhibition.…”
Section: Resultsmentioning
confidence: 49%
See 1 more Smart Citation
“…4. We have previously reported significant differences in estimated binding energies for the same compounds with these targets [12]. Here, we show that the target X-ray structure determines whether or not ligand poses reflect mixed-type inhibition.…”
Section: Resultsmentioning
confidence: 49%
“…Five X-ray structures of human AChE (PDB IDs 4EY4-4EY8, [3]) were used for docking. Rigid docking was performed with AutoDock 4.2.6 [8] as described earlier [12]. For flexible docking, Schrödinger Glide Induced Fit [13] was used with AChE as a target.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we developed a new class of selective mammalian dual binding site AChE inhibitors with an acyclic and macrocyclic structure based on 1,3-bis[ω-(substituted benzylethylamino) alkyl]-6-methyluracils. In particular, novel 6-methyl uracil derivatives with ω-(substituted benzylethylamino) alkyl chains at the N atoms of the pyrimidine ring ( Figure 1 ) were reported as selective AChE inhibitors [ 25 , 26 ]. In these compounds, the substituted electron-withdrawing nitro-, trifluoro-, and fluoro-group benzylethylamino moieties were bridged to N atoms of the 6-methyluracil moiety via various polymethylene chains.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the compounds demonstrated inhibitory power in the nanomolar range, 10,000 or more times higher than for human butyrylcholinesterase (hBChE). In vivo experiments showed that the most potent AChE inhibitor 1b improved working memory and significantly reduced the number and area of Aβ plaques in the brain of double transgenic mice expressing a chimeric mouse/human amyloid precursor protein and a mutant human presenilin 1 (APP/PS1) [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation